(untitled) (Ágora Journal, 2024)
The aim of the article is to study the dynamics of water supply in the city of Rio de Janeiro throughout the XIXth century, examining, particularly, the roles of fountain guards. Both in the colonial period and in the Empire, public fountains were built as landmarks of power in the urban world. However, numerous water carriers were still needed to complete the circuit from the water distribution points to the residences, which determined the massive presence of enslaved people in the city’s fountains. From the point of view of government agencies, this imposed the need for surveillance in the water spaces in order to maintain the equipment, but also to strictly control its visitors. It was in this context that the principles that defined the role of these public agents - the fountain guards - seem to have been shaped in the XIXth century Rio de Janeiro.